Hereditary Hemorrhagic Telangiectasia: Pregnancy and Delivery-Specific Considerations and Outcomes - Watkins, Virginia Y.; Estin, Mira L.; Craig, Amanda M.; Dotters-Katz, Sarah K.; Federspiel, Jerome J. (American Journal of Perinatology, 2024)
Prior studies have evaluated maternal outcomes in patients with hereditary hemorrhagic telangiectasia (HHT), yet pregnancy- and delivery-specific data remain limited. This study aims to evaluate pregnancy and delivery outcomes in patients with HHT.This retrospective cohort study used the Nationwide Readmissions Database to identify patients with HHT diagnosis on delivery between 2010 and 2021. The primary outcome was severe maternal morbidity (SMM). Secondary outcomes included nontransfusion SMM, preterm birth, stillbirth, prelabor rupture of membranes or preterm prelabor rupture of membranes, cesarean delivery, respiratory bleeding, cerebrovascular complications, patient disposition, and length of stay. Trends in the prevalence of HHT at delivery were assessed with logistic regression. Logistic regression analyses, adjusting for age, payer, zip code income, hospital size, and teaching status, were also used to produce adjusted relationships between HHT status and outcomes.The cohort of 21,698,861 delivered pregnancies corresponded to a national estimate of 44,325,599. Of those, 612 (national estimate: 1,265; 2.8 per 100,000) had a diagnosis of HHT. A steady rise in the HHT diagnosis rate during pregnancy from 2010 to 2021 (1.7 per 100,000 in 2010, 3.8 per 100,000 in 2021, p < 0.001 for trend) was seen. Patients with HHT were significantly more likely to experience SMM compared with patients without HHT (7.8 vs. 1.7%, adjusted relative risk [aRR]: 4.49 [95% confidence interval, CI: 3.06, 6.58]). Rates of preterm birth (14.2 vs. 8.5%, aRR: 1.57 [95% CI: 1.22, 2.03]), cesarean delivery (41.0 vs. 32.9%, aRR: 1.23 [95% CI: 1.07, 1.41]), respiratory bleeding (2.1 vs. <0.1%, aRR: 94.44 [56.64, 157.46]), and cerebrovascular complications (0.9 vs. <0.1%, aRR: 22.89 [9.89, 52.96]) were higher in patients with HHT than non-HHT patients. There was no difference in stillbirth rates between groups.Patients with HHT have higher rates of SMM and adverse delivery outcomes when compared with the baseline population.
Keywords: hereditary hemorrhagic telangiectasia; severe maternal morbidity; preterm birth; cesarean delivery